Causality Between Higher Education With Economic Growth In Indonesia - - Triyani; Tri Haryanto (MediaTrend, 2021)
The aim of this study is to investigate the causality between higher education and economic growth in Indonesia in 1980-2017. The econometric approach of this study used the Vector Auto Regressive (VAR) and Granger Causality Test. The Empirical results show evidence of unidirectional causality between higher education and economic growth in lag 1 with α of 10%. These results indicate that education as a form of investment in human resources will affect the economy. This study also shows that economic growth does not affect higher education. This unidirectional causality can be explained that the economic growth that occurs does not directly increase the overall income of the community, meaning that the positive impact of growth can only be enjoyed largely by a group of high-income people.